2022
DOI: 10.1021/acsanm.2c01832
|View full text |Cite
|
Sign up to set email alerts
|

Aromatic Carboxylic Acid Ligand Management for CsPbBr3 Quantum Dot Light-Emitting Solar Cells

Abstract: The commonly used long-chain ligands in CsPbBr3 quantum dots (QDs) hinder the electronic coupling and charge transport in optoelectronic devices; therefore, surface ligand management is crucial to optimize device performance. In this report, we demonstrate a simple and feasible aromatic carboxylic acid ligand management to obtain high-efficiency CsPbBr3 QD light-emitting solar cells (LESCs). Benzoic acid (BA) is used to replace the excess insulating ligands so that the charge transport of QD films is greatly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 49 publications
(80 reference statements)
0
11
0
Order By: Relevance
“…[2][3][4][5][6][7][8][9][10] Apart from that, CsPbBr 3 QDs have recently been investigated in depth and viewed as a promising candidate for highvoltage, wide-bandgap, and semitransparent solar cells due to their excellent phase stability and relatively large bandgaps (E g of approximately 2.4 eV). [11][12][13][14][15] Akkerman et al 11 first reported a facile room-temperature synthesis method to prepare CsPbBr 3 nanocrystals for solar cell applications, and the corresponding device exhibited a power conversion efficiency (PCE) exceeding 5% and a high open-circuit voltage (V OC ) over 1.50 V. However, in comparison with thin-film CsPbBr 3 solar cells, the efficiency of CsPbBr 3 QD solar cells is still lagging. Most of the CsPbBr 3 QD devices suffer from a low short-circuit current ( J SC ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…[2][3][4][5][6][7][8][9][10] Apart from that, CsPbBr 3 QDs have recently been investigated in depth and viewed as a promising candidate for highvoltage, wide-bandgap, and semitransparent solar cells due to their excellent phase stability and relatively large bandgaps (E g of approximately 2.4 eV). [11][12][13][14][15] Akkerman et al 11 first reported a facile room-temperature synthesis method to prepare CsPbBr 3 nanocrystals for solar cell applications, and the corresponding device exhibited a power conversion efficiency (PCE) exceeding 5% and a high open-circuit voltage (V OC ) over 1.50 V. However, in comparison with thin-film CsPbBr 3 solar cells, the efficiency of CsPbBr 3 QD solar cells is still lagging. Most of the CsPbBr 3 QD devices suffer from a low short-circuit current ( J SC ).…”
Section: Introductionmentioning
confidence: 99%
“…For further improvement in the device performance of CsPbBr 3 QD solar cells, a solution of benzoic acid in MeOAc was developed to treat CsPbBr 3 QD films, which can effectively exchange the long-chain ligands in the films, enabling increased electronic coupling, and lead to a high PCE of 5.46% with a J SC of 4.84 mA cm −2 . 15 However, during the preparation of perovskite QD solid films by layer-by-layer deposition, a short-chain carboxylate ester, especially MeOAc, is inevitably used to replace long-chain oleic acid (OA) and oleylamine (OAm) ligands. [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Methanol (MeOH) and acetic acid are produced as intermediate substances resulting from the hydrolysis of MeOAc during ligand exchange.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Luminescent nanomaterials have gained great attention among researchers in the past few years due to various applications in biological sensing, imaging and optoelectronics [1][2][3][4][5]. Many of the photoluminescent nanomaterials are semiconductors and usually contain toxic elements, heavy and expensive metals which have limited their applications.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Wang et al introduced the benzoic acid passivation to improve charge transport of quantum dots by replacing the excess insulating ligands, and the trap-assisted nonradiative recombination is also effectively inhibited. [15] Additionally, methylammonium bromide (MABr) and FABr have been used for perovskites solar cells surface passivation and obtained a decent efficiency of more than 19.1%, and 21.3%, respectively. [16][17][18][19] These findings clearly illustrate the utilization of bromide content is an important to enhance the optoelectronic properties.…”
mentioning
confidence: 99%